The ups and downs of emotional intelligence enlighten utopia - Ibarra, Luis Rodolfo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The purpose of this study is to enrich emotional intelligence theory. A contribution is made to emotional literacy by distinguishing words like impulse, affection, feeling, emotion, and affectivity. Likewise, the implications of such distinction in humanization are depicted. The research method is of a complex nature. Background information about emotional intelligence are presented; its limitations and potentialities such as the ups and downs of the psychologization of education, cognitive psychology, neuromyths, and the theory of emotional intelligence and feelings. This article calls for humanization of an altruistic humanity in the pursuit of a utopia.